An Open Source Software Suite for Multi-Dimensional Meteorological Data Computation and Visualisation. Issue 1 (11th July 2019) - Wang, Y. Q.
MeteoInfo Java software tools were developed for multi-dimensional meteorological data analysis and visualisation by integrating a Geographic Information System (GIS) and Scientific Computation Environment (SCE). Included are a Java class library for software developing, a GIS desktop application for spatial data operation and interactive multi-dimensional geoscientific data exploration, and a scientific computation and visualisation environment with Jython scripting. The popular geoscience data formats, such as NetCDF, HDF and GRIB, are supported based on a Unidata NetCDF Java library; also, its multi-dimensional array data model is used for scientific computation. In this paper, the software design framework and its implementation are presented. Furthermore, the software application capabilities are illustrated using several examples.